PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN CICIL EMAS DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA NASABAH PT PEGADAIAN CABANG MADIUN - Kasanah, Isrodiyatun (Jurnal Manajerial Bisnis, 2024)
This research examines the influence of price and promotion on purchasing decisions with purchase interest as an intervening variable at PT Pegadaian Madiun Branch.The data collection method is carried out using a questionnaire method which contains statements regarding each variable studied. The respondents of this research were gold installment customers of PT Pegadaian Madiun Branch using a sample of 40 respondents. Data analysis in this research used the SmartPLS 2.0 program. Hypothesis testing using the PLS approach is carried out in two stages, namely testing the outer model and inner model. The outer model test was carried out to prove the validity and reliability of all indicators for each variable. The inner model test was carried out to test the influence between variables according to the previously established hypothesis. The research results show that price and promotion have a significant influence on purchasing interest, price and promotion have a positive and significant influence on purchasing decisions, price and promotion have a significant influence on purchasing decisions through purchasing interest.